Effects of dietary edible bird’s nest supplementation on cognitive function of transgenerational mice - Mahaq, Obaidullah (2020)
Edible bird’s nest (EBN) is well known as a natural food product rich in glycoproteins such as sialic acid, minerals, and essential amino acids. Evidence from epidemiological studies suggests that EBN dietary supplementation improved brain cognitive functions. In mammals, the highest absorption of sialic acid from EBN occurs in the brain where it participates as an integral part of ganglioside structure in synaptogenesis and neural transmission. Sialic acid in EBN is vital during rapid brain growth particularly for preterm infants. While EBN dietary supplementation has been associated to enhance brain functions in infants, the effects of multiple generations of dietary EBN on cognitive function remain unclear. Thus, this study aimed to determine the effects of dietary EBN supplementation from different locations (e.g south (S) and north (N) of Peninsular Malaysia, Sabah (B) and commercial (C) on the cognitive function of transgenerational mice. To address these issues, C57BL/6 breeder mice (F0) were fed with different sources of EBN for six weeks (10 mg/kg) using oral gavage. Then, all animals were bred to obtain first generation (F1) until the second generation (F2) animals. At six weeks of age, F1 and F2 animals were tested for brain cognitive function by Y-maze test. Histological study for neuron density and distribution were analyzed using the hematoxylin and eosin procedure. The active compounds of EBN were determined using HPLC and the brain genes expression associated with cognitive function (e.g GNE, ST8SiaIV, SLC17A5, and BDNF mRNA) were analyzed using real-time PCR. Results showed that dietary EBN supplementation improved cognitive performance of F0, F1 and F2 mice by significantly increased the number of entries (9.04 ± 0.15; P < 0.05) and the time spent (2.40 ± 0.4 min; P < 0.05) in the novel arm of Y-maze test compared to control. This could indicate that the breeder mice (F0) absorbed sialic acid from EBN which crossed the placenta to contribute fetal brain function and development in the third trimester. In addition, EBN supplementation improved neuron development in the brain hippocampus of F0, F1 and F2 generations by significantly increased the number of neurons (32.74 ± 4.80; P < 0.05) compared to control (21.78 ± 2.86). In PCR analysis, mice maintained on EBN supplementation significantly increased the expression level of GNE (1.6-fold; P < 0.05) in both F0 and F1 of EBN-N group. Interestingly, this gene was upregulated only in F1 mice (1.64-fold) especially in the EBN-C group. Expression level of ST8SiaIV was significantly increased (2-fold; P < 0.05) in the F0 of EBN-N group and in the F1 of EBN-C group (1.83-fold). The BDNF levels were significantly increased in EBN-S (2-fold; P < 0.05), EBN-N (1.5-fold) and EBN-C (1.6-fold) F1 animals compared to control (1-fold). However, SLC17A5 expression was not significantly increased (P > 0.05) in all groups of F0 and F1 animals. These results indicate that increased number of neurons and the variation level of genes expression due to the presence and metabolism of sialic acid in mammals associates with increased cognitive performance. In conclusion, EBN extract supplementation for six weeks with higher sialic acid content improve the cognitive function of transgenerational mice.